Prediction Models of the Effect of Basin Characteristics and Forest Cover on Reservoir Sedimentation in Northeastern Thailand - Nipon Tangtham; Kosit Lorsirirat (Agriculture and Natural Resources, 1993)
Regression models for predicting the effect of basin characteristics and forest cover on reservoir sedimentation (RS) were formulated using 11 parameters, i.e., basin annual rainfall (Ra) , annual inflow (Q), areal distribution of watershed classes (WSCl-WSC5), surface area of water in resservoir (WSA; % of basin area) , basin relief ratio (Sr) , channel sinuosity (Si) and remaining forest cover (For; % ) from 11 basins in northeastern Thailand observed during 1953 to 1986. Bottom survey data from 11 reservoirs in this area are employed to find acceptable correlation between the recorded annual depositions and the mentioned parameters. The derived mathematical statistical equation is: RS = e[-7.2348+2.5386lnQ-0.0041For+K] where K = (4.442Sr -2.4077Si -0.307WSA -0.524WSC1 ). It could be postulated basing on the equation that for every 10 percent of decreasing forest area in the basin, about 4-5 percent of reservoir sedimenttation could be annually increased.